Analisis Sifat Fisik dan Magnetik Tanah di Bawah Tegakkan Pohon Kakao, Pohon Kelapa dan Jambu Mete - Rosliana Eso; La Ode Saifuddin; Sitti Kasmiati; Mardiana N; Arman Arman; Husein Husein; Tahir Tahir (University of Halu Oleo, 2022)
This study aims to analyze the physical properties of soil, such as texture, color, temperature, moisture content, bulk density and permeability as well as the magnetic properties of the soil under a tree stand of cashew, coconut and cocoa. This research was conducted on mixed farms where there are cashew, coconut and cocoa trees close to each other. Samples were taken vertically from top soil to a depth of 100 cm. The results showed that the soil color and texture of the soil under cashew, coconut and cocoa trees tended to be the same considering the locations of these three trees were very close together, but the soil texture at a depth of 50-100 cm tended to vary for these three tree species. Likewise, the water content and the ability to pass water vary from one to another following the trend of changes in bulk density and soil texture. The variation in magnetic susceptibility values which increased towards the top of the soil profile both under cashew tree stands and cocoa tree stands followed the trend of normal soil variation where superparamagnetic grain enrichment occurred and was largely influenced by pedogenesis factors. Although the magnetic properties of both are the same as well as in the paramagnetic category, the magnetic susceptibility value under cashew tree stands is greater than that under cocoa tree stands.